An Evidence-Based Roadmap for the Provision of More Equitable Telemedicine - Jelinek, Ryan; Pandita, Deepti; Linzer, Mark; Engoang, Jeremy Bikah Bi Nguema; Rodin, Holly (Applied Clinical Informatics, 2022)
Objective During the coronavirus disease 2019 pandemic, as a safety-net organization with a substantial percentage of patients of color and with limited English proficiency (LEP), we were wary of furthering health disparities in our community. We analyzed gaps in telemedicine (telephone and video) delivery in our communities, quantified the effects of our tests of change, and began the process of accumulating evidence to create a road map for other organizations.Methods We leveraged Lean problem-solving strategies to identify modifiable gaps across multiple domains that could inhibit equity in telemedicine. We implemented tests of change across domains of community engagement, technology, education, and access. We observed the proportion of telemedicine encounters across races and languages between April and November, 2020. Regression analyses tested the impact of race and language on telemedicine controlling for age, gender, insurance, and time.Results Several rounds of changes and enhancements were associated with changes in telemedicine use of +5.5% (p < 0.0001) for Hispanic, +4.0% (p < 0.0001) for Spanish-speaking, −2.1% for Black (p < 0.05), and −4.4% for White patients (p < 0.001). African-American, Hispanic, and non-English-speaking patients had between 2.3 and 4.6 times the odds of preferring telephone to video encounters (p < 0.0001), with increases in preferences for video use over time (p < 0.05).Conclusion Our roadmap to improve equitable delivery of telemedicine was associated with a significant improvement in telemedicine use among certain minority populations. Most populations of color used telephone more often than video. This preference changed over time and with equity-focused changes in telemedicine delivery.
Keywords: telemedicine; equity; Lean methods; minority populations; telemedicine and telehealth; implementation and deployment; outcome and process assessment; people; economic barriers (digital divide)